The effect of chronic guanfacine administration on high plasma vasopressin levels in essential hypertension - (:unkn) unknown (My University, 1990)
In the past several years, investigators have given evidence that vasopressin (VP), in addition to its antidiuretic function, may play an important role in cardiovascular regulation through other mechanisms. An increased plasma VP level has been reported in some patients with mild-to-moderate essential hypertension (EH). Additionally, yohimbine, a selective alpha 2-adrenoceptor antagonist, has been shown to increase the plasma VP level and blood pressure (BP) in man. The present study was performed to evaluate the effects of chronically administered guanfacine, a centrally acting alpha 2-adrenoceptor agonist, on high plasma VP levels in patients with mild-to-moderate EH in whom no other causes responsible for elevated plasma VP levels were present. The relations among VP, BP and renin-angiotensin-aldosterone system were also investigated. Eleven patients (8 women and 3 men aged 62 +/- 3 years) with untreated and uncomplicated EH were included in the study after a 2-week placebo period and kept on a diet containing 120 mmol sodium and 80 mmol potassium daily. In all patients treated once daily with 1 mg of guanfacine for 4 weeks, the drug-induced changes in plasma levels of VP and aldosterone (ALD), plasma renin activity (PRA), plasma osmolality, BP and heart rate were determined. A marked reduction in plasma VP levels (p less than 0.001) was observed and this was accompanied by a significant fall in mean arterial blood pressure (p less than 0.001). No significant changes in heart rate, plasma osmolality, PRA and plasma ALD levels were found. The results suggest that guanfacine might suppress VP secretion via alpha 2-adrenoceptors without significantly affecting renin-angiotensin-aldosterone system.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Female; Humans; Middle Aged; Male; Blood Pressure; Hypertension; Renin; Aldosterone; Guanfacine; Guanidines; Osmolar Concentration; Phenylacetates; Vasopressins